2021
DOI: 10.2147/jir.s332134
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effect of Flavonoid Extract from the Peel of Gonggan (Citrus reticulata Blanco Var. Gonggan) on CCl4-Induced Acute Liver Injury in Mice

Abstract: Citrus peel, a waste product of citrus consumption and processing, is rich in flavonoids. This study aimed to study the protective effect of flavonoid extract from the peel of gonggan (Citrus reticulata Blanco var. gonggan) on acute chemical liver injury. Materials and Methods:We established a chemical liver injury model induced by carbon tetrachloride (CCl 4 ) in mice. The flavonoid composition in gonggan (Citrus reticulata Blanco var. gonggan) peel was detected by HPLC. The histopathological sections of live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 52 publications
(63 reference statements)
0
7
0
Order By: Relevance
“…In comparison, NOB administration increased antioxidant ability and elevated TAS in liver tissues. It has been reported that NOB protects cells against hydrogen-peroxide-prompted damage by decreasing malonaldehyde (MDA), scavenging ROS, and increasing GSH and SOD contents [ 11 ]. It may be due to the healing ability of the NOB, which decreased TOS and ultimately increased TAS in the liver tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, NOB administration increased antioxidant ability and elevated TAS in liver tissues. It has been reported that NOB protects cells against hydrogen-peroxide-prompted damage by decreasing malonaldehyde (MDA), scavenging ROS, and increasing GSH and SOD contents [ 11 ]. It may be due to the healing ability of the NOB, which decreased TOS and ultimately increased TAS in the liver tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids have attracted much attention during the last few years [ 7 ]. Nobiletin (NOB) is a polymethoxy-flavone extracted from a variety of citrus fruits, which has attracted much attention due to its several health-promoting effects, such as antioxidant [ 10 ], anti-inflammatory [ 11 ], anti-diabetic, and anti-cancer [ 12 ]. Furthermore, numerous investigations have indicated that NOB plays a defensive role in the nervous system, kidney, and heart [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…TC berry is characterized by its pleasant flavor and attractive appearance. Moreover, the abundance of carbohydrate, fiber, protein, and calcium in TC fresh has promoted the cultivation of TC for daily needs and disease remedy in the form of a traditional herb to a certain degree ( 1 ). The output of TC was 0.32 million tons in 2020, most of the TC had generally been eaten fresh, and approximately a third of TC was processed into drinks or distilled into liquor.…”
Section: Introductionmentioning
confidence: 99%
“…However, the liver is susceptible to damage induced by exogenous materials, such as alcohol, drugs, and other hepatotoxic chemicals, resulting in liver dysfunction [ 1 , 2 ]. Chemical liver damage, which often aggravates hepatocirrhosis, liver failure, and cancer, is among the most common types of liver injury observed clinically and is a significant burden on the global public health system [ 3 , 4 ]. Currently, many synthetic chemical medicines are widely used to relieve liver injury, although they may cause adverse effects, such as gastrointestinal irritation and weight gain [ 5 ].…”
Section: Introductionmentioning
confidence: 99%